P-66 Development of an advance care planning training programme utilising online learning. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Kirk, Mary; O'Connor, Stephen; Hart, Matt; Black, Racheal; McCarthy, Ali; Keith, Suzz
Abstract : The project involved development of an online learning programme to enable early discussions about patient preferences at the end of life. The developed training programme has a broad focus on planning for future care and death with information regarding dementia, care homes, mental capacity and the importance of future planning and the legal aspects of planning individual needs and wishes. The project group using best evidence and developed separate units within the programme. This training enables Advance care planning, preventing inappropriate referral or admission to acute services; it aims to reduce the pain, anxiety and distress of those people whose focus is on cure rather than care; and an increase inthe locus of control which patients and family members can exert over the dying process. This project worked on the basis of 'no decision about me without me', aiming to help individuals to be better informed about their deteriorating disease, consulted about their preferences with regard to end of life care and to have opportunity to discuss options with those responsible for their care. The project was innovative in bringing together community services, specialist palliative care providers from across Kent and Canterbury Christchurch University with funding secured from Health Education Kent, Surrey and Sussex to work collaboratively to develop the online training programme which is accessible to all via the University Website. The programme can be accessed at http://www.canterbury.ac.uk/health-and-wellbeing/advance-care-planning/home.aspx References: Leadership Alliance for the Care of Dying People (2014) One chance to get it right Mind. Mental Capacity Act 2005, 2013 Moriarty J, Rutter D, Ross PD, Holmes P. End of life care for people with dementia living in care homes, SCIE Research Briefing 40 . London: Social Care Institute for Excellence, 2012 DOH. Advance care planning, 2008 Francis R. Mid Staffordshire NHS Foundation Trust, 2013 GMC. Treatment and Care towards the End of Life, 2010 Gold Standards Framework, 2014 Department of Constitutional Affairs. Mental capacity act 2005 code of practice . London: The Stationary Office, 2007 Department of Health. Advance care planning: a guide for health and social care staff . London: Department of Health, 2007 General Medical Council. Consent: patients and doctors making decisions together . London: General Medical Council, 2008 Royal College of Physicians. Concise guidance to good practice Number 12: advance care planning . London: Royal College of Physicians, 2009